Design and Implementation System Automatic Guided Vehicle (AGV) Using RFID for Position Information - Waldy, Ibnu; Rusdinar, Angga; Estananto, Estananto (Universitas Telkom, 2015)
Manufactured goods distribution system is a very important part in the production chain. Delivery of goods from one point to another point affects the effectiveness of the production process. At the moment, most companies whose business are in manufacturing require automation, including distribution of goods. One application of automation in the distribution of goods is AGV (Automated Guided Vehicle). Companies need AGV that can move in complex pathways. The movement includes a selection of AGV path traversed and AGV terminal position. This research discusses the design and implementation of an AGV navigation and position information settings. AGV navigation uses fuzzy logic in its algorithm, while position setting of the AGV uses Radio Frequency Identification (RFID) to recognize the position of the robot at each terminal. From the testing result, the system obtained a success rate of 96% in movement of the robot from one terminal to another terminal using the RFID. RFID can be read at both speed of the robot i.e. 6.9 and 7.13 m/min